Tahap motivasi dan pencapaian usahawanan : satu kajian kes ke atas usahawan kecil melayu MARA,Melaka - Osman, Idris (2004)
The aim of this research is to identify the level of motivation dan achievement among small Malay entrepreneurs who rented MARA’s building complex at Jalan Hang Tuah, Malacca. Around 40 small Malays entrepreneurs were involved in this research which conducted varieties of small business scale. Using the Maslows Hirarchy Need Theory, this research shown that there are exists a relationship between level of motivation and achievement. Self-esteem need was identify as the most motivational factor that influence the entrepreneurship activity of respondents. Analysis shows that the level of motivation among respondents being high as a whole. The findings found that the respondents appreciate the humanistic value while conducting their business. Family and community support had helped them toward a high achievement as well as they’re worthy experiences. As a conclusion, to grab a high achievement in their business, small Malay entrepreneurs need to fulfill a high level of motivation to be a successful entrepreneur.